The Materiobiology of Silk: Exploring the Biophysical Influence of Silk Biomaterials on Directing Cellular Behaviors - Kochhar, Dakshi; DeBari, Megan K.; Abbott, Rosalyn D. (Frontiers in Bioengineering and Biotechnology, 2021)
Biophysical properties of the extracellular environment dynamically regulate cellular fates. In this review, we highlight silk, an indispensable polymeric biomaterial, owing to its unique mechanical properties, bioactive component sequestration, degradability, well-defined architectures, and biocompatibility that can regulate temporospatial biochemical and biophysical responses. We explore how the materiobiology of silks, both mulberry and non-mulberry based, affect cell behaviors including cell adhesion, cell proliferation, cell migration, and cell differentiation. Keeping in mind the novel biophysical properties of silk in film, fiber, or sponge forms, coupled with facile chemical decoration, and its ability to match functional requirements for specific tissues, we survey the influence of composition, mechanical properties, topography, and 3D geometry in unlocking the body’s inherent regenerative potential.